Bilayer TPU films integrating pH-responsive bromocresol purple–fluorescein indicators and carvacrol/tea tree oil-loaded HKUST-1@alkaline lignin: Visualization, controlled release, and meat preservation - Liuzi Du; Xiaodong Zhai; Xinyang Han; Ke Zhang; Junjun Zhang; Xiaobo Zou; Zhihua Li; Zhikun Yang; Quancai Sun; Ye Peng; Xiaowei Huang (Food Research International, 2026)

Probabilistic assessment of post-earthquake running safety threshold for high-speed railway bridge based on nonparametric copula method - Yan Zhang; Guangsong Song; Hui Jiang; Junjun Guo; Qikai Sun; Yun Shan (Soil Dynamics and Earthquake Engineering, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Enhancing treatment performance for agricultural runoff in ecological ditches through synergistic effects of denitrifying phosphate-accumulating bacteria and natural/synthetic media - Yonggui Zhao; Xiaoyun Sun; Bohua Ji; Ying Peng; Jingzhi Mao; Chenyu Zeng; Rui Yang; Junjun Chang (Journal of Cleaner Production, 2026)

Integrated chemometrics and untargeted metabolomics reveal the differential effects of drying methods on the quality of Sharen (Amomum villosum Lour.) - Zhixia Sun; Jun Chen; Junjun He; Ivan Shorstkii; Liqing Du; Taotao Dai; Yihui Wang; Yanli Yao; Chengmei Liu; Lizhen Deng (Food Bioscience, 2026)

Carbohydrates: How structural features influence digestion-fermentation kinetic parameters - Ge Zhang; Li Cao; Zhiqiang Sun; Jingyi Huang; Qi Zhu; Lee J. Johnston; Zeyu Zhang; Junjun Wang; Jinbiao Zhao (Food Chemistry, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Early cotton topping increases peanut yield without sacrificing cotton yield through reducing interspecific competition under intercropping - Junjun Nie; Yanan Li; Zhenhuai Li; Shizhen Xu; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Lin Sun; Jianlong Dai; Yanjun Zhang; Hezhong Dong (Field Crops Research, 2026)

Elucidating the mechanism of sulfur reactions over NiFe2O4 oxygen carrier at atomic level - Cheng Shen; Yu Li; Daifen Chen; Xin Liu; Junjun Sun; Jintian He; Laihong Shen (Fuel, 2025)

Shading-induced canopy cooling alleviates waterlogging damage during flowering by disrupting heat synergism in field-grown cotton - Yanjun Zhang; Yabin Yuan; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Interactively Integrating Reach and Grasp Information in Macaque Premotor Cortex - Junjun Chen; Guanghao Sun; Yiwei Zhang; Weidong Chen; Xiaoxiang Zheng; Shaomin Zhang; Yaoyao Hao (Neuroscience Bulletin, 2025)

Ni-doped CdO/CdSe in-situ heterojunctions: Tunable composition engineering for low-concentration formaldehyde detection - Yunjiang Zhang; Yan Zhang; Junjun Sun; Jianliang Cao; Cong Qin; Yan Wang (Journal of Hazardous Materials, 2025)

Identifying the optimal flow conditions of a fishway with two entrances for endemic fishes at a high-altitude hydropower station in the Tibetan Himalaya, China - Sicheng Zeng; Junjun Tan; Junjian Sun; Yuanyang Wang; Giri Raj Kattel; Xiaotao Shi (Ecological Engineering, 2025)

Mitigating waterlogging-induced yield loss in cotton through removal of early fruits: Agronomic and physiological mechanisms - Yanjun Zhang; Shen Qiu; Tiantian Liang; Shizhen Xu; Zhenhuai Li; Zhengpeng Cui; Lijie Zhan; Dongmei Zhang; Junjun Nie; Lin Sun; Jianlong Dai; Hezhong Dong (Field Crops Research, 2025)

Effects of dietary long-chain polyunsaturated fatty acids on osmoregulation and salinity adaptation in red tilapia (Oreochromis mossambicus♀ × O. niloticus♂) under salinity stress - Jiaying Xie; Junjun Sun; Yuanyou Li; Shuqi Wang; Douglas R. Tocher; Cuihong You; Zhenqiang An; Dizhi Xie; Cuiying Chen (Fish Physiology and Biochemistry, 2025)

Supramolecular self-assembling IGF-1 nanofibers modulate neutrophil extracellular traps to accelerate diabetic wound healing - Xuebo Wei; Tengfei Qi; Qizhi Shuai; Ying Zhang; Yun Xu; RuiYang Sun; ZhuoYang Song; Junjun Luo; Yinnan Zhang; Hongyu Zhang; Chunqiu Zhang; Jie Gao; et al. (Chemical Engineering Journal, 2025)

Solvent-free green preparation of PVDF/ PPTA-pulp hollow fiber membrane and construction of the multi-porous structure - Haolong Xue; Junjun Sun; Dawei Ji; Zhengjie Yue; Xiaocao Zhao; Yizhe Ding; Huiru Zheng; Changfa Xiao (Chemical Engineering Journal, 2025)

An Adaptive Neural Network Fuzzy Sliding Mode Controller for Tracking Control of Deep-Sea Mining Vehicles - Shidong Wang; Zida Shan; Jialuan Xiao; Junjun Cao; He Zhang; Nan Sun (Journal of Marine Science and Engineering, 2025)
Traditional track-driven deep-sea nodule mining solutions significantly disrupt seabed ecosystems, making them unsuitable for commercial application. In contrast, ROV-like alternatives, such as the hovering mining vehicle, or HMV, offer substantial improvement in this regard and are deemed to be a viable way forward. This paper proposes an adaptive neural network fuzzy sliding mode controller architecture for the underwater trajectory tracking of HMV. The algorithm, named the Adaptive Radial Basis Function Neural Network Fuzzy Sliding Mode Controller (ARFSMC), replaces modeled vehicle dynamics with a radial basis function neural network (RBFNN). To enhance disturbance rejection, an adaptive mechanism is applied to the RBFNN output weighting matrix. Additionally, a fuzzy inference system (FIS) is implemented as the switching term, replacing the traditional signum function, to reduce high-frequency oscillations in the control signal. The stability of the algorithm under unknown external disturbance was confirmed via Lyapunov stability analysis. To validate the ARFSMC’s performance, three numerical simulation cases were conducted, each designed to reflect an expected operation scenario of the HMV, through which the tracking performance of the ARFSMC under time-varying system inertia is validated and benchmarked against conventional sliding mode control (CSMC) and double-loop sliding mode control (DSMC). The simulation results confirm that comparing the above two controllers, the root mean square error (RMSE) of the ARFSMC is reduced by 15.0% and 11.4%, respectively. And when comparing the CSMC, the chattering is reduced by 97.8%. Both indicate their high robustness and superior performance in tracking control. The controller development and numerical validation in this work are aimed at the trajectory tracking challenge of the HMV in deep-sea mining operation. The dynamical modeling of the vehicle is based on parameters of the HaiMa ROV. External disturbance from currents were considered as sinusoidal functions modified with random noise.

Impact of stochastic collisions on cloud droplet number concentration and relative dispersion during Meiyu frontal system - Jingxi Sun; Chunsong Lu; Yan Yin; Sinan Gao; Junjun Li; Yiwei Zhang (Atmospheric Research, 2025)

Self-Assembled Arachidonic Acid Nanomicelles for Radiation-Induced Ferroptosis to Enhance Tumor Radioimmunotherapy - Jiadong Wang; Yueyue Jing; Li Liu; Pengfei Xing; Zheng Deng; Yifan Zhang; Xirui Wu; Bin Hu; Cai Zhang; Xianglong Sun; Yuqian Liu; Jiawei Liu; et al. (Chemical Engineering Journal, 2025)

Identification and validation of a novel nine-gene prognostic signature of stem cell characteristic in hepatocellular carcinoma - Yahang An; Weifeng Liu; Yanhui Yang; Zhijie Chu; Junjun Sun (Journal of Applied Genetics, 2025)

Bromodomain and extraterminal domain (BET) promote autophagy in buffalo sertoli cells - Yuan Yang; Junjun Zhang; Yue Zhang; Qinqiang Sun; Ruixin Liu; Chunrong Xu; Peng Xu; Yangqing Lu; Qiang Fu (Theriogenology, 2025)

Cerebrospinal Fluid-Derived extracellular Vesicle-Inspired Multifunctional bone regeneration scaffold for cranial defect repair - Jie He; Yifan Zhang; Xiaolan Sun; Minjie Wang; Qing Zhang; Simin Liu; Shaojie Yu; Xuan Wang; Zhenxing Wang; Junjun Li; Xiaobin Jiang (Chemical Engineering Journal, 2025)

Unveiling the role of intrinsic defects in N/S Co-Doped hard carbon for superior sodium-ion batteries - Yunlei Yang; Chang Liu; Junjun Yao; Zhenqi Tang; Ying Sun; Kun Zhang; Hui Li; Tianyi Ma; Jieshan Qiu (Chemical Engineering Journal, 2025)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

Study on the characteristics of urban background ozone pollution based on long-term observations from mountain sites in China during 2015–2022 - Wei Zhao; Bo Gao; Junjun Deng; Jiaren Sun; Laiguo Chen; Shaojia Fan (Atmospheric Research, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Experimental and theoretical study on performance of Cu-Fe spinel supported with certain inerts during chemical looping combustion - Yu Li; Li Wang; Daifen Chen; Jing Liu; Wei Fan; Junjun Sun (Chemical Engineering Journal, 2024)

Integration of surface-based and space-based atmospheric CO2 measurements for improving carbon flux estimates using a new developed 3-GAS inversion model - Shu'an Liu; Xiaofeng Pan; Xiangyun Xiong; Tianle Sun; Lin Xue; Huifang Zhang; Junjun Fang; Jingchun Fang; Guchun Zhang; Hui Xu; Baozhang Chen (Atmospheric Research, 2024)

SNX14 inhibits autophagy via the PI3K/AKT/mTOR signaling cascade in breast cancer cells - Sha Lv; Hongyan Jiang; Lingyan Yu; Yafei Zhang; Liangliang Sun; Junjun Xu (Journal of Molecular Histology, 2024)

Enhancing stand establishment and yield formation of cotton with multiple drip irrigation during emergence in saline fields of Southern Xinjiang - Jianlong Dai; Zhengpeng Cui; Yanjun Zhang; Lijie Zhan; JunJun Nie; Jianqiang Cui; Dongmei Zhang; Shizhen Xu; Lin Sun; Bing Chen; Hezhong Dong (Field Crops Research, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Simultaneous removal of nitrate, phosphate and Cr(VI) in groundwater by iron‑carbon-based constructed wetlands: Performance intensification by organic solid amendments - Ting Sun; Mingda Hu; Yuxuan Li; Qingfeng Bi; Jinlong Zheng; Pengchang Duan; Junjun Chang (Journal of Water Process Engineering, 2024)

Devonian integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Wenkun Qie; Kun Liang; Wen Guo; Biao Gao; Junjun Song; Bo Chen; Pu Huang; Li Qiao; Honghe Xu; Jitao Chen; Yucong Sun; Yichun Zhang (Science China Earth Sciences, 2024)

Utilizing machine learning for reactive material selection and width design in permeable reactive barrier (PRB) - Yangmin Ren; Mingcan Cui; Yongyue Zhou; Shiyu Sun; Fengshi Guo; Junjun Ma; Zhengchang Han; Jooyoung Park; Younggyu Son; Jeehyeong Khim (Water Research, 2024)

9,9′-epoxylignans from Syringa pinnatifolia: A typical case of stereochemical assignment by a quantum chemical calculation with MAEΔΔ parameter - Shungang Jiao; Changxin Liu; Panlong Chen; Junjun Li; Jingjing Sun; Xiaoli Gao; Xingyun Chai (Phytochemistry, 2024)

Combined treatment with pre-aeration and carrier addition strengthens the purification performance of a deep pilot-scale duckweed-based pond - Yonggui Zhao; Jinquan Li; Yuejiao Yang; Ruidong Ma; Ying Peng; Xiaoyun Sun; Siwei Gao; Junjun Chang; Changqun Duan (Journal of Water Process Engineering, 2024)

A ratiometric fluorescence amine sensor based on carbon quantum dot-loaded electrospun polyvinylidene fluoride film for visual monitoring of food freshness - Wenjun Song; Xiaodong Zhai; Jiyong Shi; Xiaobo Zou; Yuhong Xue; Yue Sun; Wei Sun; Junjun Zhang; Xiaowei Huang; Zhihua Li; Tingting Shen; Yanxiao Li; et al. (Food Chemistry, 2024)

Response of growth performance and cecum microbial community to cyclic heat stress in broilers - Junjun Yuan; Yan Li; Shiang Sun; Jiaying Wu; Jin Zhou; Shaojun He (Tropical Animal Health and Production, 2024)

The incidence of asthma attributable to temperature variability: An ecological study based on 1990–2019 GBD data - Qingsong Xu; Qinfeng Zhou; Junjun Chen; Tong Li; Junxiong Ma; Runming Du; Mintao Su; Jing Li; Ming Xu; Shengzhi Sun; Jing Ma; Murugappan Ramanathan; et al. (Science of The Total Environment, 2023)

Natural resource endowment and its lmpact on ecological efficiency - Yi Sun; Junjun Gao (Resources Policy, 2023)

Sonoelectrochemical system mechanisms, design, and machine learning for predicting degradation kinetic constants of pharmaceutical pollutants - Yongyue Zhou; Yangmin Ren; Mingcan Cui; Fengshi Guo; Shiyu Sun; Junjun Ma; Zhengchang Han; Jeehyeong Khim (Chemical Engineering Journal, 2023)

Terminal removal at first square enhances vegetative branching to increase seedcotton yield at low plant density - Junjun Nie; Lin Sun; Lijie Zhan; Xue Li; Wenting Hou; Yanjun Zhang; Weijiang Li; Dongmei Zhang; Zhengpeng Cui; Zhenhuai Li; Shizhen Xu; Jianlong Dai; et al. (Field Crops Research, 2023)

Enhanced metal−promoter interaction over Na modified Co2C nanoprisms for high-efficiency hydrogen production from methanol steam reforming - Zilong Shao; Shunan Zhang; Chaojie Huang; Haozhi Zhou; Junjun Chen; Yuhan Sun; Hui Wang (Chemical Engineering Journal, 2023)

Phase-mediated mercury removal from water using multilayered molybdenum disulfide: The key role of redox mechanism - Jia Sun; Junjun Pei; Zhiyuan Qiu; Jing Guo; Bo Li; Kaixing Fu; Kai Yin; Shenglian Luo (Journal of Cleaner Production, 2023)

Comparison of effects of multiple oxidants with an ultrasonic system under unified system conditions for bisphenol A degradation - Shiyu Sun; Yangmin Ren; Fengshi Guo; Yongyue Zhou; Mingcan Cui; Junjun Ma; Zhengchang Han; Jeehyeong Khim (Chemosphere, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

A visual bi-layer indicator based on mulberry anthocyanins with high stability for monitoring Chinese mitten crab freshness - Xiaowei Huang; Liuzi Du; Zhihua Li; Jin Xue; Jiyong Shi; Haroon Elrasheid Tahir; Xiaodong Zhai; Junjun Zhang; Ning Zhang; Wei Sun; Xiaobo Zou (Food Chemistry, 2023)

Lattice stain dominated hydrazine oxidation reaction in single-metal-element nanosheet - Jie Shi; Qintao Sun; Wenxiang Zhu; Tao Cheng; Fan Liao; Mengjie Ma; Junjun Yang; Hao Yang; Zhenglong Fan; Mingwang Shao (Chemical Engineering Journal, 2023)

Preparation of CeVO4/BNNS catalyst and its application in oxidation desulfurization of diesel oil - Xinyu Li; Junjun Shi; Jiangang Wang; Lei Xi; Rui Sun; Fan Zhang; Xi Wu; Zhiyong Zhou; Zhongqi Ren (Fuel, 2023)

Effect of preferential delignification on xylooligosaccharides production from poplar by acetic acid/sodium acetate hydrolysis - Hong Liao; Junjun Zhu; Fubao Fuelbiol Sun; Zhina Lian; Yong Xu; Junhua Zhang (Journal of Cleaner Production, 2023)

Ridge intertillage alters rhizosphere bacterial communities and plant physiology to reduce yield loss of waterlogged cotton - Yanjun Zhang; Shizhen Xu; Guangya Liu; Tengxiang Lian; Zhenhuai Li; Tiantian Liang; Dongmei Zhang; Zhengpeng Cui; Lijie Zhan; Lin Sun; Junjun Nie; Jianlong Dai; et al. (Field Crops Research, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Involvement of LARP7 in Activation of SIRT1 to Inhibit NF-κB Signaling Protects Microglia from Acrylamide-Induced Neuroinflammation - Jinxiu Guo; Hongjia Xue; Haitao Zhong; Wenxue Sun; Shiyuan Zhao; Junjun Meng; Pei Jiang (Neurotoxicity Research, 2022)

Characterization and Phylogenetic Analysis of the Complete Mitochondrial Genome of Saturnia japonica - Jiang Liu; Junjun Dai; Jinjin Jia; Yemei Zong; Yahao Sun; Ying Peng; Lei Wang; Cen Qian; Baojian Zhu; Guoqing Wei (Biochemical Genetics, 2022)

Devonian-Carboniferous boundary in China - Wenkun Qie; Yuanlin Sun; Wen Guo; Ting Nie; Bo Chen; Junjun Song; Kun Liang; Baoan Yin; Shupeng Han; Junying Chang; Xiangdong Wang (Palaeobiodiversity and Palaeoenvironments, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Astragaloside protects rat brain from microwave-induced functional injuries via restoring acetylcholine and normalizing electroencephalogram - Li Zhao; Yunbo Sun; Chao Yu; Junjun Chen; Xinping Xu; Xueyan Zhang; Hui Wang; Jing Zhang; Haoyu Wang; Ji Dong; Binwei Yao; Hongmei Zhou; et al. (Environmental Science and Pollution Research, 2020)

The miR-15/16 Cluster Is Involved in the Regulation of Vertebrate LC-PUFA Biosynthesis by Targeting pparγ as Demonostrated in Rabbitfish Siganus canaliculatus - Junjun Sun; Cuiying Chen; Cuihong You; Yang Liu; Hongyu Ma; Óscar Monroig; Douglas R. Tocher; Shuqi Wang; Yuanyou Li (Marine Biotechnology, 2020)

Microbial responses to inorganic nutrient amendment overridden by warming: Consequences on soil carbon stability - Mengmeng Wang; Junjun Ding; Bo Sun; Junyu Zhang; Kristen N. Wyckoff; Haowei Yue; Mengxin Zhao; Yuting Liang; Xiaoyue Wang; Chongqing Wen; Jizhong Zhou; Yunfeng Yang (Environmental Microbiology, 2018)
Summary Eutrophication and climate warming, induced by anthropogenic activities, are simultaneously occurring worldwide and jointly affecting soil carbon stability. Therefore, it is of great interest to examine whether and how they interactively affect soil microbial community, a major soil carbon driver. Here, we showed that climate warming, simulated by southward transferring Mollisol soil in agricultural ecosystems from the cold temperate climate zone (N) to warm temperate climate (C) and subtropical climate zone (S), decreased soil organic matter (SOM) by 6%–12%. In contrast, amendment with nitrogen, phosphorus and potassium enhanced plant biomass by 97% and SOM by 6% at the N site, thus stimulating copiotrophic taxa but reducing oligotrophic taxa in relative abundance. However, microbial responses to nutrient amendment were overridden by soil transfer in that nutrient amendment had little effect at the C site but increased recalcitrant carbon‐degrading fungal Agaricomycetes and Microbotryomycetes taxa derived from Basidiomycota by 4‐17 folds and recalcitrant carbon‐degrading genes by 23%–40% at the S site, implying a possible priming effect. Consequently, SOM at the S site was not increased by nutrient amendment despite increased plant biomass by 108%. Collectively, we demonstrate that soil transfer to warmer regions overrides microbial responses to nutrient amendment and weakens soil carbon sequestration.

Stability assessment of a new antithrombotic small peptide, Arg-Gly-Asp-Trp-Arg (RGDWR), and its derivative - Lijun Yang; Litao Zhang; Lihong Yan; Haifeng Zheng; Peifen Lu; Junjun Chen; Jie Dai; Haibiao Sun; Yong Xu; Tao Yang (Biotechnology Letters, 2017)

Land scale biogeography of arsenic biotransformation genes in estuarine wetland - Si‐Yu Zhang; Jian‐Qiang Su; Guo‐Xin Sun; Yunfeng Yang; Yi Zhao; Junjun Ding; Yong‐Shan Chen; Yu Shen; Guibing Zhu; Christopher Rensing; Yong‐Guan Zhu (Environmental Microbiology, 2017)
Summary As an analogue of phosphorus, arsenic (As) has a biogeochemical cycle coupled closely with other key elements on the Earth, such as iron, sulfate and phosphate. It has been documented that microbial genes associated with As biotransformation are widely present in As‐rich environments. Nonetheless, their presence in natural environment with low As levels remains unclear. To address this issue, we investigated the abundance levels and diversities of aioA , arrA , arsC and arsM genes in estuarine sediments at low As levels across Southeastern China to uncover biogeographic patterns at a large spatial scale. Unexpectedly, genes involved in As biotransformation were characterized by high abundance and diversity. The functional microbial communities showed a significant decrease in similarity along the geographic distance, with higher turnover rates than taxonomic microbial communities based on the similarities of 16S rRNA genes. Further investigation with niche‐based models showed that deterministic processes played primary roles in shaping both functional and taxonomic microbial communities. Temperature, pH, total nitrogen concentration, carbon/nitrogen ratio and ferric iron concentration rather than As content in these sediments were significantly linked to functional microbial communities, while sediment temperature and pH were linked to taxonomic microbial communities. We proposed several possible mechanisms to explain these results.

Soil organic matter quantity and quality shape microbial community compositions of subtropical broadleaved forests - Junjun Ding; Yuguang Zhang; Mengmeng Wang; Xin Sun; Jing Cong; Ye Deng; Hui Lu; Tong Yuan; Joy D. Van Nostrand; Diqiang Li; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2015)
As two major forest types in the subtropics, broadleaved evergreen and broadleaved deciduous forests have long interested ecologists. However, little is known about their belowground ecosystems despite their ecological importance in driving biogeochemical cycling. Here, we used Illumina MiSeq sequencing targeting 16S rRNA gene and a microarray named GeoChip targeting functional genes to analyse microbial communities in broadleaved evergreen and deciduous forest soils of Shennongjia Mountain of Central China, a region known as ‘The Oriental Botanic Garden’ for its extraordinarily rich biodiversity. We observed higher plant diversity and relatively richer nutrients in the broadleaved evergreen forest than the deciduous forest. In odds to our expectation that plant communities shaped soil microbial communities, we found that soil organic matter quantity and quality, but not plant community parameters, were the best predictors of microbial communities. Actinobacteria , a copiotrophic phylum, was more abundant in the broadleaved evergreen forest, while Verrucomicrobia , an oligotrophic phylum, was more abundant in the broadleaved deciduous forest. The density of the correlation network of microbial OTU s was higher in the broadleaved deciduous forest but its modularity was smaller, reflecting lower resistance to environment changes. In addition, keystone OTU s of the broadleaved deciduous forest were mainly oligotrophic. Microbial functional genes associated with recalcitrant carbon degradation were also more abundant in the broadleaved deciduous forests, resulting in low accumulation of organic matters. Collectively, these findings revealed the important role of soil organic matter in shaping microbial taxonomic and functional traits.

The Effect of Streptozotocin and Alloxan on the mRNA Expression of Rat Hepatic Transporters In Vivo - Ting Zhai; Junjun Wang; Lijuan Sun; Yong Chen (AAPS PharmSciTech, 2015)

Osteochondral regeneration by a bilayered construct in a cell-free or cell-based approach - Zheng Cao; Shuxun Hou; Daming Sun; Xiaoning Wang; Junjun Tang (Biotechnology Letters, 2012)

Eco-toxic effects of sulfadiazine sodium, sulfamonomethoxine sodium and enrofloxacin on wheat, Chinese cabbage and tomato - Caixia Jin; Qiuying Chen; Ruilian Sun; Qingxiang Zhou; Junjun Liu (Ecotoxicology, 2009)